Parallel Homochiral and Anti‐Parallel Heterochiral Hydrogen‐Bonding Interfaces in Multi‐Helical Abiotic Foldamers - Mazzier, Daniela (Angew Chem Int Ed Engl, 2019)
A hydrogen‐bonding interface between helical aromatic oligoamide foldamers has been designed to promote the folding of a helix‐turn‐helix motif with a head‐to‐tail arrangement of two helices of opposite handedness. This design complements an earlier helix‐turn‐helix motif with a head‐to‐head arrangement of two helices of identical handedness interface. The two motifs were shown to have comparable stability and were combined in a unimolecular tetra‐helix fold constituting the largest abiotic tertiary structure to date.